Associations of leisure‐time physical activity and active school transport with mental health outcomes: A population‐based study. (30th December 2022) - Jussila, Juuso J.; Pulakka, Anna; Ervasti, Jenni; Halonen, Jaana I.; Mikkonen, Santtu; Allaouat, Sara; Salo, Paula; Lanki, Timo
Abstract : Promoting physical activity can improve population health. This study aimed to examine associations of leisure‐time moderate‐to‐vigorous physical activity and active school transport with mental health, that is, symptoms of depression and anxiety, among 15‐ to 16‐year‐old adolescents. We also assessed the relationships with less‐studied outcomes, such as chronic stress and visits to school psychologist. A nationwide Finnish cohort of eighth and ninth graders from the School Health Promotion study (32 829 participants; mean age 15.4 years; 53% girls) was studied. We used logistic regression to estimate odds ratios (OR), with models adjusted for major sociodemographic, health behavior, and physical activity variables. Key findings suggest that leisure‐time moderate‐to‐vigorous physical activity is associated with better mental health in a dose–response manner. Even the smallest dose, 30 weekly minutes, was linked to 17% lower odds of chronic stress symptoms compared to inactivity (OR 0.83, 95% CI 0.71–0.96). Compared to non‐active transportation, more than 30 min of daily active school transport yielded 19% (OR 1.19, 95% CI 1.07–1.31) and 33% (OR 1.33, 95% CI 1.12–1.58) higher odds of depression symptoms and school psychologist visits, respectively. However, no associations were found for low‐to‐moderate daily active school transport levels (<30 min). This large‐scale study further highlights a positive association between leisure‐time physical activity and mental health among youth. Future research should explore what factors might explain the potential adverse mental health outcomes of active school transport.